CircHIPK3: Key Player in Pathophysiology and Potential Diagnostic and Therapeutic Tool - Zhou, Jiang; Wang, Baisheng; Bin, Xin; Xie, Changqing; Li, Bo; Liu, Ousheng; Tang, Zhangui (Frontiers in Medicine, 2021)
A large number of studies in China and other countries have confirmed that circularHIPK3 (circHIPK3) plays an important role in the pathophysiological processes of various diseases. Through the action of sponge miRNA (miR), circHIPK3 regulates cell proliferation, differentiation, and migration, and plays a key role in disease processes. By referring to a large number of research reports, this article explores the specific functional role of circHIPK3 in fibrotic diseases, cancer, and other diseases. This review aims to clarify the role of circHIPK3 in disease processes in order to aid further studies into the specific pathogenesis and clinical diagnosis of various diseases and provide new ideas for treatments.